HIV post‐exposure prophylaxis in community settings and by lay health workers or through task sharing: a systematic review of effectiveness, case studies, values and preferences, and costs - Caitlin E. Kennedy; Rahel Dawit; Ping Teresa Yeh; Michelle Rodolph; Nathan Ford; Heather‐Marie A. Schmidt; Robin Schaefer; Rachel Baggaley; Virginia Macdonald (Journal of the International AIDS Society)
Abstract Introduction Post‐exposure prophylaxis (PEP) for HIV prevention has been inadequately promoted, provided and used. Expanded access and task sharing could increase the HIV prevention impact of PEP, but scientific evidence to inform programmatic and policy decisions has not been synthesized. Methods To inform World Health Organization guidelines, we conducted a systematic review of studies examining the provision of PEP in community settings, and by trained lay health workers or through task sharing. We searched CINAHL, PsycINFO, PubMed, EMBASE and scientific conferences for studies published between January 2012 and October 2023. We screened abstracts and extracted data in duplicate. The effectiveness review included randomized controlled trials and comparative observational studies; risk of bias was assessed using Cochrane Collaboration and Evidence Project tools, and the certainty of the evidence was assessed using GRADE. We also summarized implementation case studies, values and preferences studies, and cost and cost‐effectiveness studies. Results For provision of PEP in community settings, we identified one effectiveness study, three case studies, one values and preferences study, and one cost study. Very low certainty evidence from one study in Kenya and Uganda suggested that PEP uptake, when offered as part of a dynamic prevention package, was highest in the community setting (vs. outpatient or antenatal care settings). For provision of PEP by trained lay health workers or task sharing, we identified three effectiveness studies, two case studies, four values and preferences studies, and one cost study. Very low certainty evidence from Kenya, Uganda and the United States suggested that engagement of lay providers or pharmacists increased PEP uptake and completion and decreased HIV acquisition. Studies from six countries found most health workers supported PEP provision by non‐specialist providers. One modelling study suggested community‐based provision may be cost‐effective or cost‐saving in Africa. Discussion Evidence on expanding PEP access through community delivery or task sharing is limited but generally suggests positive outcomes, feasibility, acceptability and cost‐effectiveness of these approaches. Indirect evidence from HIV treatment and pre‐exposure prophylaxis further supports these approaches. Conclusions Programmes should be expanded to include community delivery and task sharing to dispense, distribute, provide and monitor PEP.